Yukawa fluids: a new solution of the one component case - Blum, L.; Hernando, J.A. (Condensed Matter Physics, 2003)
In recent work a solution of the Ornstein-Zernike equation for a general
Yukawa closure for a single component fluid was found. Because of the
complexity of the equations a simplifying assumption was made, namely
that the main scaling matrix Γ had to be diagonal. While in principle this
is mathematically correct, it is not physical because it will violate symmetry
conditions when different Yukawas are assigned to different components.
In this work we show that by using the symmetry conditions the off diagonal
elements of Γ can be computed explicitly for the case of two Yukawas
solving a quadratic equation: There are two branches of the solution of this
equation, and the physical one has the correct behavior at zero density.
The non-physical branch corresponds to the solution of the diagonal approximation.
Although the solution is different from the diagonal case, the
excess entropy is formally the same as in the diagonal case. В сучасних роботах знайдено розв’язок рівняння Орнштейна-Церніке для простого однокомпонентного плину в рамках узагальнених
умов замикання Юкави. У зв’язку зі складністю рівнянь було зроблено припущення про те, що головна скейлінгова матриця Γ має
бути діагональною. Хоча це математично правильно, фізично це порушує умови симетрії при співставлянні різних потенціалів Юкави
різним компонентам. В цій роботі ми показуємо, що використовуючи умови симетрії, недіагональні елементи матриці Γ можуть бути
точно обчислені, розв’язуючи квадратне рівняння для двох потенціалів Юкави. Існують два розв’язки цього рівняння, але тільки один з
них має фізично правильну поведінку при нульовій густині. Нефізичний розв’язок відповідає розв’язку з діагональною апроксимацією.
I хоча наш розв’язок відрізняється від того, що в діагональному випадку, надлишкова ентропія формально залишається такою ж.